Pengaruh Sistem Informasi Akuntansi Dan Kualitas Informasi Terhadap Kepuasan Klien Pengguna Jasa Akuntan (Studi Empiris Pada Kantor Jasa Akuntan Terampil Di Kota Gorontalo) - Rusdi Abdulkarim; Pemy Christiaan (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2021)
This study aims to see and measure how much influence the Quality of Accounting Information Systems and Quality of Information on Client Satisfaction is carried out at the Trampil Accountant Services Office located in Gorontalo City, with a sample of 64 clients. Data collection techniques using questionnaires and using multiple regression as a method of data analysis. The result of the research states that the quality of the accounting information system and the quality of information has an influence on client satisfaction, either simultaneously or partially. Based on research data, the Quality of Accounting Information Systems (X1) partially has an effect of 0.593 on Client Satisfaction (Y) while Information Quality (X2) has a partial effect of 0.337 on Client Satisfaction (Y) and the rest is the influence of other variables that are not researched